Psikologi Anak = The pshycology of the child / Jean Piaget , Barbel Inhelder ; penyunting Eka Adi Nugraha ; Penerjemah Tifatul Jannah - Piaget, Jean; Eka Adi Nugraha Tifatul Jannah (2010)
XVII, 185 hlm 23 cm